2017
DOI: 10.2147/ijn.s126199
|View full text |Cite
|
Sign up to set email alerts
|

Corneal permeation properties of a charged lipid nanoparticle carrier containing dexamethasone

Abstract: Drug delivery carriers can maintain effective therapeutic concentrations in the eye. To this end, we developed lipid nanoparticles (L/NPs) in which the surface was modified with positively charged chitosan, which engaged in hydrogen bonding with the phospholipid membrane. We evaluated in vitro corneal permeability and release characteristics, ocular irritation, and drug dynamics of modified and unmodified L/NPs in aqueous humor. The size of L/NPs was uniform and showed a narrow distribution. Corneal permeation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 47 publications
6
31
0
Order By: Relevance
“…1 Ban et al developed positively charged chitosan (CTS)-coated solid lipid nanoparticles with high ocular bioavailability, which was ascribed to the electrostatic interaction between the positively charged nanoparticles and the negatively charged ocular surface. 11 Furthermore, CTS derivatives, especially thiolated CTS, with good mucoadhesivity and enhanced trans-cornea drug penetration have been widely used in topical ocular drug delivery. 12 Up to now, no previous work has been reported to enhance corneal permeability by ocular influx transporters with nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ban et al developed positively charged chitosan (CTS)-coated solid lipid nanoparticles with high ocular bioavailability, which was ascribed to the electrostatic interaction between the positively charged nanoparticles and the negatively charged ocular surface. 11 Furthermore, CTS derivatives, especially thiolated CTS, with good mucoadhesivity and enhanced trans-cornea drug penetration have been widely used in topical ocular drug delivery. 12 Up to now, no previous work has been reported to enhance corneal permeability by ocular influx transporters with nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Ban et al modified dexamethasone-loaded lipid nanoparticles made of soy/lecithin by chitosan coating and observed that the modification resulted in a 1.5-fold increase in apparent permeability coefficient of the drug dexamethasone [194]. The chitosan-modified lipid nanoparticles increased the dexamethasone ocular bioavailability more than the unmodified ones in rabbits with C max , T max and AUC 0–24 h increasing 2.37-, 12 and 4.69-fold vs. 1.17-, 10 and 2.12-fold, respectively in comparison to dexamethasone eye drops [194].…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%
“…The chitosan-modified lipid nanoparticles increased the dexamethasone ocular bioavailability more than the unmodified ones in rabbits with C max , T max and AUC 0–24 h increasing 2.37-, 12 and 4.69-fold vs. 1.17-, 10 and 2.12-fold, respectively in comparison to dexamethasone eye drops [194]. Liu et al evaluated liquid crystalline nanoparticles (LCNP) for the delivery of tetrandrine using components including glyceryl monoolein, poloxamer 407, water, Gelucire 44/14 and amphipathic octadecyl-quaternized carboxymethyl chitosan [195].…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%
“…The amount of drug in the sample was determined via the HPLC method as described in the "Analysis of encapsulation efficiency" section. The cumulative permeation per area of the scar tissue (Q n , μg/cm 2 ) was calculated according to the following formula, 24 with the in vitro transdermal release curve plotted with time (hour) as the abscissa and Q n (μg/cm 2 ) as the ordinate:…”
Section: In Vitro Evaluation Of Transdermal Permeationmentioning
confidence: 99%